RECEPTIVE AND PRODUCTIVE KNOWLEDGE OF LEXICAL COLLOCATIONS IN THAI UNIVERSITY LEARNERS OF ENGLISH - Zhang, Xulong; Sukying, Apisak (European Journal of English Language Teaching, 2021)
The present study investigates lexical collocations in first- and fourth-year Thai university learners’ and examines the relationship between receptive and productive knowledge of lexical collocations. A total of 148 students (75 first-year students and 73 fourth-year students) were tested on their lexical collocations, both receptively and productively, using two measures. Descriptive and inferential statistics were used to analyze the quantitative data, and correlational analysis determined the relationship between receptive and productive knowledge. Overall, the results showed that Thai university learners achieved significantly higher performance on tests of receptive knowledge of lexical collocations than on tests of productive knowledge. The data analysis also indicated that the fourth-year learners outperformed the first-year learners on both receptive and productive measures of lexical collocations. Furthermore, the correlational analysis revealed that receptive and productive knowledge of lexical collocations were interrelated. Together, the current findings indicate that Thai university learners’ productive knowledge of lexical collocations is built on receptive knowledge, and lexical collocations result from incremental learning.   Article visualizations: